Metabolic signature of methylone in primary mouse hepatocytes, at subtoxic concentrations - Araújo, Ana Margarida (2021)
Methylone (3,4-methylenedioxymethcathinone) is one of the most popular new psychoactive drugs worldwide. Although advertised as a safe drug, its use has been associated to several cases of liver damage. In this work, a metabolomics approach based on gas chromatography-mass spectrometry (GC-MS) combined with chemometric analyses was used to characterize the disturbances occurring in the intra- and extracellular metabolome of primary mouse hepatocytes exposed to two subtoxic concentrations (LC01 and LC10) of methylone to better understand the early hepatotoxic events. Results showed a characteristic metabolic fingerprint for methylone, where aspartate, cysteine, 2-methyl-1-pentanol, 4-methylheptane, dodecane, 2,4-dimethyl-1-heptene, 1,3-di-tert-butylbenzene, acetophenone, formaldehyde and glyoxal levels were significantly changed at both concentrations tested. Furthermore, subtoxic concentrations of methylone caused profound changes in several biochemical pathways, suggesting adaptations in energy production processes (TCA cycle, amino acids metabolism and pyruvate metabolism), cellular antioxidant defenses (glutamate, cysteine and glutathione metabolism) and hepatic enzymes (associated to hydrocarbons, alcohols, aldehydes and ketones metabolism). This metabolic response to the initial methylone challenge most probably reflects the activation of protective mechanisms to restore cellular homeostasis. Overall, this study highlights the potential of untargeted metabolomic analysis to reveal the hepatic metabolic signature of methylone at subtoxic concentrations, and also provides clues to clarify the early mechanisms underlying the toxicity triggered by this new psychoactive substance, opening a new perspective for the study of toxicity mechanisms of new xenobiotics.